Praktek Income Smoothing Ditinjau dari Cash Holding, Bonus Plan, Kepemilikan Institusional dan Profitabilitas - Sari Fadillah; Elvira Luthan (Jurnal Akademi Akuntansi, 2023)
Purpose: This study aims to examine the effect of cash holding, bonus plans, institutional ownership, and profitability on income smoothing in financial sector companies listed on the Indonesia Stock Exchange. Methodology/approach: The  research  data  is  sourced  from  the Annual  Report  and  Share Price Information of  Finacial Companies Listed  on  the  IDX  (Indonesian  Stock  Exchange)  2017-2021.  The analytical method uses logistic regression by SPSS 26. Findings: The results show that cash holding and bonus plan have no significant effect on income smoothing. Meanwhile, institutional ownership and profitability have signuficant effect on income smoothing Practical and Theoretical contribution/Originality: The implication of this research is expected to  help  investors and shareholders to understand the factors that can maximize management behavior to do income smoothing on financial statement. In addition,  potential  investors  are  expected  to  be  able  to  use  the findings  of  this  study  to  help  them  assess  the  condition  of  the company   before   making   investment   decisions. Novelty   of   this research is focusing on the financial sector as a sample whereas previous research only focused on the non-financial sector. Research Limitation: Future studies may be useful to use other variables to income smoothing examined to provide a newly additional finding.